Analysis of the Management of Facilities and Infrastructure at the South Sulawesi Province Office of Communication, Informatics, Statistics, and Encryption - Fadillah, Nur; Jamaluddin, Jamaluddin; Isgunandar, Isgunandar (Pinisi Journal of Officers Review, 2025)
This study aims to analyze the management of facilities and infrastructure at the Diskominfo-SP Office of South Sulawesi Province, as well as identify the supporting and inhibiting factors involved in this management. This study uses a qualitative approach with a descriptive research type that focuses on the management of facilities and infrastructure based on procurement, storage, maintenance, and inventory indicators. The data collection techniques used are observation, interviews, and documentation. The study's results indicate that the management of facilities and infrastructure at the Communication, Informatics, Statistics, and Encryption Office of South Sulawesi Province is considered "excellent." This is shown through management indicators, namely: (1) Procurement is carried out by looking at the priority scale of needs, starting from the procurement process through the planning stages, which include needs analysis, fund planning, and employee selection. Procurement is carried out using an e-catalog system to ensure budget efficiency and transparency. (2) Storage is carried out by maintaining neatness and conducting periodic checks on the condition of the storage cabinet. Because there is no storage warehouse, empty rooms are used temporarily as a solution. However, this leads to less effective storage management, which impacts the efficiency and safety of goods. (3) Maintenance is carried out in a structured manner with regular planning, implementation, and cleaning every two months. Supervision is carried out by giving responsibility to the team and monitoring the results of maintenance. (4) Inventory is carried out with a combination of manual and digital approaches; using software can make recording easier even though there is no special application. Regular checks are also carried out to assess whether assets need to be repaired, replaced, or kept in use. Overall, management is effective with this method.